THE IMPACT OF DIGITAL FINANCIAL TECHNOLOGIES ON ISLAMIC INSURANCE AND OTHER FINANCIAL INSTITUTIONS: OPPORTUNITIES AND CHALLENGES - Dildora Abdusalimovna Muradova (Journal of Artificial Intelligence and Digital Economy, 2024)
This article explores the transformative impact of digital financial technology (FinTech) on Islamic insurance (Takaful) and other financial institutions. It examines the unique opportunities and challenges associated with FinTech innovation in the context of Islamic finance, characterized by adherence to Shariah principles. The study examines the integration of digital technologies such as blockchain, artificial intelligence (AI) and big data analytics to improve operational efficiency, customer experience and regulatory compliance. In addition, it addresses specific issues facing Islamic financial institutions, including Shariah compliance, cybersecurity risks, and the digital divide. The results highlight the need for a strategic approach to leveraging FinTech for sustainable growth in the Islamic finance sector.